Fluid evolution of Au-Cu zones in Um Balad area, North Eastern Desert of Egypt: Implications from mineral chemistry and fluid inclusions. (July 2018) - Abd El Monsef, Mohamed; Salem, Ibrahim; Slobodník, Marek; Ragab, Ahmed
Abstract: Scanning electron microscope (SEM), Electron microprobe (EMPA) and fluid inclusion studies of the ore body, as well as geochemical analyses of country rocks were performed to determine the nature and characteristics of the mineralizing fluid responsible for Au-Cu deposits in Um Balad area, Northern Eastern Desert of Egypt. The Um Balad Au-Cu deposits are confined to well developed-quartz veins and veinlets cutting through the hosting country rocks. Petrographic and geochemical investigations of the hosting rocks distinguished between two main rock units; 1) metagabbro-diorite rocks with tholeiitic nature derived in island arc/continental margin tectonic regime, and 2) granodiorite rocks formed from calc-alkaline magma in continental margin regime. Wallrock alterations are represented by propylitic and argillic types. The mineralized quartz veins are striking in NE-SW direction and dipping between (35°–45°) in SE direction, other mineralized mafic dykes enriched with auriferous quartz veinlets are trending NE-SW and dipping 70°/SE. The main ore minerals are represented by gold, chalcopyrite, pyrite, sphalerite, malachite, covellite and goethite. While, geffroyite, cuprite, chrysocolla, pseudomalachite, britholite, wolframite, scheelite, hematite and rutile are detected as minor constituents. Fluid inclusions microthermometry and isochore calculations combined with chlorite geothermometry revealed that the Um Balad deposits were formed at temperature ranging from 305 °C to 325 °C and pressure between (100–500 bar). The mineralization had been developed in the shallow levels, beneath the water table at depth of 350–1760 m, rather than common mesothermal vein-type deposits in Egypt. Magmatic water have been suggested as the main source for the mineralized fluid. The transportation of the gold metal seems to be happen as bisulfide complexes in moderately acidic environment. The deposition was resulted from combination of changes in physico-chemical parameters, temperature and pressure plus the instability of the reduced sulfur complexes. A contamination with metamorphic and/or meteoric water was also proposed that has strong influence during the depositional process. Graphical abstract: Image Highlights: The gold-copper deposits in Um Balad are found in form of mineralized quartz veins and veinlets filling fractures and open spaces within metagabbro-diorite rocks and in vicinity to intrusive masses of granodiorite. Metagabbro-diorite rocks are of tholeiitic nature that was formed in island arc/continental margin tectonic regime. While, granodiorites have calc-alkaline affinity developed in active continental margin. Mineral chemistry and fluid inclusions data revealed depositional conditions of: temperature between (305–325 °C); pressure between (100–500 bar) and depth in range of (350–1760 m). Magmatic-metamorphic/meteoric waters has been suggested as a source for the mineralized fluids. In which, the intrusion of granodiorite supplied the Au-Cu lode as well as the sufficient heat for the fluid circulation process.